The Rising Price of Physicians' Services: A Correction and Extension on Supply - Brown, Douglas M. (The Review of Economics and Statistics, 1994)
The effect of changing prices on the supply of physicians' services has important policy implications. In this note, a correction of previous work on supply by the author in this shows that with aggregate data the price elasticity of supply is zero. However, using individual physician data in the context of a utility-maximizing model of supply, it is found that the price elasticity of supply is about -0.2. This result could portend serious problems ahead for recently enacted Medicare pricing strategies to contain physician spending. Copyright 1994 by MIT Press.